Teacher Racism, Academic Self‐Concept, and Multiculturation: Investigating Adaptive and Maladaptive Relations With Academic Disengagement and Self‐Sabotage for Indigenous and Non‐Indigenous Australian Students. (5th April 2012) - Bodkin‐Andrews, Gawaian H; Denson, Nida; Bansel, Peter
<x xml:space="preserve">Abstract</x> The issue of patterns of educational disengagement for Indigenous Australian students has long been of considerable concern within Indigenous education research. Although there is an expanding research base identifying factors that may increase (or decrease) the risk of disengagement for Indigenous students, little acknowledgement has been given to international research highlighting how stigma and discrimination may be associated with student disengagement and the resiliency factors that may nullify these associations. Utilising a sample of 1, 376 (305 Indigenous; 1, 071 non‐Indigenous) students from five New South Wales high schools in Australia, this study sought to examine the influence of academic self‐concept and two culturally sensitive constructs—specifically, perceived multiculturation (perceived cultural respect) and racial discrimination—on two disengagement‐orientated outcomes: affective disengagement and self‐sabotaging behaviour (behavioural disengagement) for both Indigenous and non‐Indigenous students. The findings showed relatively consistent direct and positive effects of academic self‐concept and direct negative effect of teacher racism for both groups of students. An interaction effect (discrimination × multiculturation) for the Indigenous students only was also identified, which suggested that the negative effects of racial discrimination on self‐sabotaging behaviour are exacerbated when the Indigenous students perceived higher levels of cultural respect from others. Overall, while these findings suggest that promoting higher levels of inter‐cultural respect may be beneficial for Indigenous and non‐Indigenous alike (e.g., culturally inclusive programmes), such positive perceptions may put Indigenous students at greater risk if the impact of racism is not also addressed. The implications of these findings suggest that cultural safety must be framed both in promoting the positive (cultural respect) and in eliminating the negative (racism).